2016
DOI: 10.1136/bcr-2015-213620
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid hyperemesis syndrome

Abstract: SUMMARYThe antiemetic properties of marijuana are well known, but there is increasing evidence of its paradoxical hyperemetic effects on the gastrointestinal tract and central nervous system, known as 'cannabinoid hyperemesis syndrome' (CHS). We report a case of CHS encountered in our outpatient clinic. We also completed a review of the literature using PubMed in patients over 18 years of age with CHS. Understanding the diagnostic criteria and risk factors associated with CHS may reduce the ordering of unneces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Our review of the literature identified a total of 25 case series (n = 271) and 105 individual case reports of patients identified with CHS (Table ) . Most of the reported case series and case studies predated the publication of Rome IV criteria for CHS.…”
Section: Resultsmentioning
confidence: 99%
“…Our review of the literature identified a total of 25 case series (n = 271) and 105 individual case reports of patients identified with CHS (Table ) . Most of the reported case series and case studies predated the publication of Rome IV criteria for CHS.…”
Section: Resultsmentioning
confidence: 99%
“…Cannabinoid hyperemesis syndrome (CHS) has been well described in the literature 6870. The symptoms of CHS include significant nausea, violent vomiting, and abdominal pain in the setting of chronic cannabis use.…”
Section: Introductionmentioning
confidence: 99%
“…Cannabis is the most widely used recreational substance worldwide. Marijuana is currently legal in some states for medicinal uses, while some states have legalized it for recreational use [ 1 ]. In Nepal, ethnomedicine has been practiced for generations and cannabis has been utilized in isolated tribes to treat diarrhea, constipation, and snake bites.…”
Section: Introductionmentioning
confidence: 99%